Intra-Arterial, but Not Intrathecal, Baclofen and Codeine Attenuates Cough in the Cat - Olsen, Wendy L.; Rose, Melanie; Golder, Frank J.; Wang, Cheng; Hammond, Julie C.; Bolser, Donald C. (Frontiers in Physiology, 2021)
Centrally-acting antitussive drugs are thought to act solely in the brainstem. However, the role of the spinal cord in the mechanism of action of these drugs is unknown. The purpose of this study was to determine if antitussive drugs act in the spinal cord to reduce the magnitude of tracheobronchial (TB) cough-related expiratory activity. Experiments were conducted in anesthetized, spontaneously breathing cats (n=28). Electromyograms (EMG) were recorded from the parasternal (PS) and transversus abdominis (TA) or rectus abdominis muscles. Mechanical stimulation of the trachea or larynx was used to elicit TB cough. Baclofen (10 and 100 g/kg, GABA-B receptor agonist) or codeine (30 g/kg, opioid receptor agonist) was administered into the intrathecal space and also into brainstem circulation via the vertebral artery. Cumulative doses of intrathecal baclofen or codeine had no effect on PS, abdominal muscle EMGs or cough number during the TB cough. Subsequent intra-arterial administration of baclofen or codeine significantly reduced magnitude of abdominal and PS muscles during TB cough. Furthermore, TB cough number was significantly suppressed by intra-arterial baclofen. The influence of these drugs on other behaviors that activate abdominal motors pathways was also assessed. The abdominal EMG response to noxious pinch of the tail was suppressed by intrathecal baclofen, suggesting that the doses of baclofen that were employed were sufficient to affect spinal pathways. However, the abdominal EMG response to expiratory threshold loading was unaffected by intrathecal administration of either baclofen or codeine. These results indicate that neither baclofen nor codeine suppress cough via a spinal action and support the concept that the antitussive effect of these drugs is restricted to the brainstem.